1989
DOI: 10.1111/j.1365-2044.1989.tb11223.x
|View full text |Cite
|
Sign up to set email alerts
|

Propofol—fentanyl anaesthesia for coronary artery surgery and cardiopulmonary bypass

Abstract: SummaryA two-stage propofol infusion combined with fentanyl was w e d to maintain anaesthesia during coronary artery surgery in patients with good ventricular function. Whole blood propojol concentrations were measured at frequent intervals; plasma protein binding was measured before, during and after cardiopulmonary bypass. An initial infusion rate of 10 mg/kg/hour provided good protection from the pressor response to sternotomy. A predictable steady state concentration was achieved in the prebypass period wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 16 publications
3
34
0
3
Order By: Relevance
“…This is in accordance with a previous study during deep hypothermia (25-27°C) for cardiopulmonary bypass in heart surgery (Russell et al, 1989). However, a study in healthy volunteers (34 6 0°C) showed reduced intercompartmental clearances, but not reduced CL tot , during TH (Leslie et al, 1995).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is in accordance with a previous study during deep hypothermia (25-27°C) for cardiopulmonary bypass in heart surgery (Russell et al, 1989). However, a study in healthy volunteers (34 6 0°C) showed reduced intercompartmental clearances, but not reduced CL tot , during TH (Leslie et al, 1995).…”
Section: Discussionsupporting
confidence: 79%
“…No significant differences in the activity of CYP2C were seen in a study on rats, but the clearance of phenytoin (CYP2C9 and CYP2C19) was reduced by 67% (Iida et al, 2001;. Propofol blood concentrations were increased by approximately 20% both in healthy volunteers at 34°C and during hypothermic cardiopulmonary bypass, likely due to reduced intercompartmental clearances in the former (Russell et al, 1989;Leslie et al, 1995). In summary, reduced elimination during hypothermia has been shown for morphine, midazolam, and fentanyl in both animals and man (Koren et al, 1987;Bansinath et al, 1988;Fukuoka et al, 2004;Fritz et al, 2005).…”
Section: Introductionmentioning
confidence: 91%
“…ml -~ was achieved within 15 min of starting the infusion (4 mg. kg-t-hr-l) and remained constant throughout surgery. Russell et al 23 though reported a decreased plasma propofol concentration at the onset of CPB with a gradual rise in propofol level during the hypothermic period. Rewarming during CPB caused a gradual decline to prebypass plasma propofol concentration.…”
Section: Repeated Boluses or Constant Infusionmentioning
confidence: 99%
“…However, hypothermic CPB increases the distribution volume of propofol [29,30] and may lead to sequestration of propofol by the CPB circuit [31]. In addition, metabolism of propofol may be decreased, and haemodilution and heparin administration increase the protein unbound fraction of propofol [29]. Therefore, it is difficult to predict the changes of free propofol concentration during CPB.…”
Section: Discussionmentioning
confidence: 97%
“…The target control infusion system normally produces small discrepancies between the calculated and actual blood concentrations with a bias (the mean prediction error) of ¹2%, and precision (the mean of the individual absolute prediction errors) of 15.1% [28]. However, hypothermic CPB increases the distribution volume of propofol [29,30] and may lead to sequestration of propofol by the CPB circuit [31]. In addition, metabolism of propofol may be decreased, and haemodilution and heparin administration increase the protein unbound fraction of propofol [29].…”
Section: Discussionmentioning
confidence: 99%